Pregnancy outcome of women with gestational diabetes in a tertiary level hospital of North India - Pikee Saxena; Swati Tyagi; Anupam Prakash; Aruna Nigam; Shubha Sagar Trivedi (Wolters Kluwer Medknow Publications, 2011)
Background: Women with gestational diabetes mellitus (GDM) pose an important public health problem because diabetes not only affects the maternal and fetal outcome, but these women and their fetuses are also at an increased risk of developing diabetes and related complications later in their life. Objectives: The study was conducted to determine the maternal and fetal outcomes of 50 diabetic vs 50 normoglycemic pregnancies. Materials and Methods: This was a retrospective analytical record-based study conducted in a tertiary level hospital. Detailed information regarding maternal, fetal, and labor outcome parameters was recorded in a prestructured proforma and compared in normoglycemic and diabetic pregnancies. Results: Patients with obesity, history of diabetes in the family, spontaneous abortions, and gestational diabetes in previous pregnancies had a greater incidence of GDM in current pregnancy (P<0.05 for all). Hypertension, polyhydramnios, macrosomia, fetopelvic disproportion, and cesarean sections were more (P<0.001) among diabetic pregnancies. Congenital anomalies, polycythemia, hypocalcemia, and hyperbilirubinemia were also observed to be more (P<0.05) in neonates born to diabetics, suggesting an adverse effect of hyperglycemia in utero. Conclusion: Diabetes during pregnancy is associated with higher maternal and fetal morbidity. Therefore, early screening, detection, close monitoring, and intervention is essential to reduce maternal and fetal short- and long-term adverse effects, especially in high-risk groups. Pregnancy provides an opportunity to the clinician to control the disease process and inculcate healthy lifestyle practices in these patients.